2008
DOI: 10.1002/cjoc.200890407
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Highly Selective Resonance Scattering Spectral Assay for Trace Carcinoembryonic Antigen

Abstract: Gold nanoparticles, in size of 10 nm, were used to label monoclonal carcinoembryonic antigen antibody (CEAAb) to obtain an immunonanogold resonance scattering (RS) spectral probe (AuCEAAb) for the measurement of trace carcinoembryonic antigen (CEA). In pH 6.8 Na 2 HPO 4 -NaH 2 PO 4 buffer solution and the presence of polyethylene glycol (PEG)-6000, the AuCEAAb combined with CEA to form the nanogold-labeled immunocomplex clusters in average size of 227 nm, which exhibited two scattering peaks at about 320 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recently, the resonance scattering (RS) spectral method has been widely used in monitoring trace metal ions and some other organic/inorganic molecules, such as antigens, melamine, protein, and DNA, because of its simplicity, rapidity, sensitivity, and low cost . Tao and his co-workers revealed that the RS technique combined with an inorganic catalyst can amplify the response signals, which can significantly enhance the sensitivity and selectivity of the method .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the resonance scattering (RS) spectral method has been widely used in monitoring trace metal ions and some other organic/inorganic molecules, such as antigens, melamine, protein, and DNA, because of its simplicity, rapidity, sensitivity, and low cost . Tao and his co-workers revealed that the RS technique combined with an inorganic catalyst can amplify the response signals, which can significantly enhance the sensitivity and selectivity of the method .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Recently, some immunoreaction, nanogold labeled immunoreaction and immunonanogold catalytic reaction have been utilized to establish some new RS methods for detection of antigen and haptene. [21][22][23][24] In addition, the combining RS technique with inorganic catalytic reaction and enzyme catalytic reaction was applied to analysis of trace inorganic ion, organic compound and enzyme activity. For example, using the enzyme catalytic effect, an enzyme catalytic-RS method for lysozyme activity was established.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has used protein and aptamer to modify AuNPs, based on their good biocompatibility. Combined with the RS effect of AuNPs, we have established immunoanalysis 24,25 and aptamer analysis 26,27 to detect specific targets. Furthermore, we have improved the sensitivity by integrating aptamer analysis with AuNP-catalysis.…”
Section: Introductionmentioning
confidence: 99%